Primary idiopathic systemic amyloidosis - rare classical cases with fatal outcome - Shivakumar Patil; Supraja Chinthala; Snehal Lunge (Our Dermatology Online, 2016)
Primary systemic amyloidosis is a rare condition. We report two cases of primary systemic amyloidosis. Both the cases were without any hematological abnormality. Cutaneous features were the predominant presenting symptoms in these patients. The patients presented with typical waxy lesions on face and macroglossia. Diagnosis was confirmed by histopathology with haematoxylin and eosin staining and Congo red staining